STUDY OF REHABILITATION OF ONCOGYNECOLOGICAL DISEASES AMONG THE POPULATION AND EVIDENCE-BASED MEDICINE IN DIAGNOSTICS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Oncogynecological diseases represent a significant public health challenge due to their high morbidity, complex clinical course, and substantial impact on quality of life. This study aims to analyze the role of evidence-based medicine in the diagnosis and rehabilitation of oncogynecological diseases among the population. The assessment is based on contemporary clinical guidelines, systematic reviews, and high-quality clinical studies evaluating diagnostic accuracy, treatment outcomes, and rehabilitation effectiveness in gynecologic oncology. Particular attention is given to evidence-based diagnostic algorithms, imaging and biomarker utilization, and multidisciplinary rehabilitation approaches addressing physical, psychological, and social aspects of recovery. The findings indicate that the integration of evidence-based diagnostic strategies enables earlier detection and more accurate disease staging, while rehabilitation programs supported by robust clinical evidence significantly improve functional outcomes, treatment tolerance, and quality of life. The results underscore that comprehensive implementation of evidence-based medicine across diagnostic and rehabilitative stages is essential for optimizing outcomes and reducing the long-term burden of oncogynecological diseases.
Keywords: Oncogynecological diseases; evidence-based medicine; early diagnosis; rehabilitation; clinical guidelines; quality of life